Clinical Knesiology and Anatomy - Lippert, Lynn, 1942-; Minor, Mary Alice D., 1944-; Towler, Christopher D.; Minor, Scott Duesterhaus (Philadelphia : F.A. Davis Company, 2023)
"This book represents the fundamental principles of kinesiology and clinical anatomy. Several changes are incorporated in the seventh edition. Biomechanics, an important foundation of kinesiology, is presented earlier in the text. And certain content related to anatomy of the human body has been reordered so it is covered in chapters specific to its anatomical location"--
Basic information -- Basic biomechanics -- Skeletal system -- Articular system and arthrokinematics -- Nervous system -- Muscular system -- Circulatory system -- Head and temporomandibular joint -- Neck and trunk -- Pelvis -- Respiratory system -- Shoulder girdle -- Shoulder joint -- Elbow joint -- Wrist joint -- Hand - Hip joint - Knee joint - Leg, ankle, and foot -- Posture -- Gait.
Includes bibliographical references and index.
Keywords: Movement; Kinesiology, Applied; Musculoskeletal System -- anatomy & histology; Physical Therapy Modalities